Growth performance and carcass merit of japanese quails (Coturnix japonica) fed with sorghum as an energy source substitute for maize in North Western Nigeria - Tamburawa (2023)
A feeding trial was conducted to determine the growth performance and carcass characteristics of Japanese quails fed diets containing sorghum. A total of ninetyof one-week old Japanese quail chicks were used for the experiment. Five diets were formulated in which sorghum was included at graded levels 0, 15, 30, 45 and 60% dietary levels designated as treatment 1, 2, 3, 4 and 5 respectively.The experimental period was five weeks when the birds reach six weeks of age. The results of the growth performance showed significant differences (P<0.05) in the final body weight (161.70 –180.10g) and daily feed intake (21.34–25.12g).Significant (P<0.05) differences was also observed in all carcass parameters measured except for dressing percentage. Liver weight and large intestine with T5 (65% total replacement) recorded the highest means value of 6.00g and 6.66g.Non-significant high values of feed conversion ratio were also obtained among the treatments. Treatment 1 (0%) and Treatment 5 (60%) showed better results in all parameters measured compared to other treatments. In conclusions, sorghum grain can play a significant role in formulating quail feed and can completely (60%) be used to replace maize without affecting the performance and carcass yield of the quails